Comparison of the structure and properties between single quench+temper and double quench+temper of mediumcarbon and carbonmanganese steel - Yurianto, Yurianto; Sulardjaka, Sulardjaka; Widyanto, Susilo Adi; Yanuar, Padang (Eastern-European Journal of Enterprise Technologies, 2020)
Quenched and tempered steels are needed for highly-stressed structures in military and non-military equipment. This paper was written for studying the structure and properties (hardness and impact energy absorbed) of medium-carbon and carbon-manganese steels before and after Quench+Temper and Double Quenched+Tempered. Because water is cheap and easy to control, it was used as a quenching medium. This study compares the hardness and impact energy absorbed of quenched plus tempered and double quenched plus tempered steels. The results showed that double quenched plus tempered steel hardness was higher than in quenched plus tempered steels. Besides, the grain structure is refiner than that of quenched plus tempered steel. The taking of the austenite temperature and holding time is essential because of the hardness at the end of the quenching process. The study aims to obtain hardness and impact energy from quenching+tempering and double quenching+tempering of medium-carbon and carbon-manganese steel for armor steel. In the first step, five specimens were heated at 900 ℃ (held for 30 minutes), cooled in freshwater and produced Q900 Steel. Then, these specimens were heated at 750 ℃, 800 ℃, 850 ℃, and 900 ℃, held for 30 minutes and provided Q900+750 Steel, Q900+800, Q900+850 Steel, and Q900+900 Steel. These specimens were tempered at 150 ℃ (held for 30 minutes) and produced Q900+750&T Steel, Q900+800&T Steel, Q900+850&T Steel, Q900+900&T Steel. Martensite reached the cooling period 357 ℃ to 182 ℃, tempered at 150 ℃ (held for 30 minutes). Hardness for double-quenching and tempering is higher than for conventional. The maximum impact energy of double-quenching and tempering heat treatment of Q900+850&T steel is suitable for armor steel used